The academic english language needs of industrial design students in UiTM Kedah, Malaysia - Adzmi, Nor Aslah; Bidin, Samsiah; Ibrahim, Syazliyati; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2009)
The purpose of this study was to analyse the academic English language lacks and needs of Industrial Design students in Universiti Teknologi MARA Kedah (UiTM). It highlights the lacks and needs for English for Academic Purposes in helping the students to succeed in the program through the usage of English language. The research tools used were in the form of a questionnaire and interview which later being computed using SPSS into data analysis. Results indicated that the students have problems in acquiring the English language skills. This shows the weaknesses of English Language courses in helping the students to acquire the language skills needed by the faculty. The study concludes that relevant actions should be taken as to ensure the needs of the students are fulfilled and they can perform effectively in the program and future career.